Pengaruh Motivasi Kerja, Kepemimpinan Partisipatif, dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Dinas Perdagangan Kabupaten Alor - Theresia Lounggina Luisa Peny; Alvonso Fanisius Gorang; Hermayanti Hermayanti (Peneliti.net, 2023)
Performance is the result of work achieved by an employee or employees in carrying out their duties following the responsibilities given to them. Factors that influence performance in this study include work motivation, participatory leadership, and organizational culture. This study aims to determine: the effect of work motivation, participatory leadership, and organizational culture on employee performance at the Alor Regency Trade Office where there are still some problems in carrying out their duties and responsibilities they have not achieved maximum goals. In this study, researchers used several previous studies that had been carried out by other people with the same variables and several indicators proposed by experts. This research uses quantitative research methods. The population in this study was 35 employees at the Alor District Trade Office. Instrument trials were carried out with validity and reliability tests and several classical assumption tests were used, namely normality, heteroscedasticity, multicollinearity, and linearity. Meanwhile, to determine the effect of the independent variables on the dependent variable, multiple linear regression analysis was used, using the t-test to determine the effect part and the F-test to determine the effect simultaneously. Data was taken by distributing questionnaires to employees at the Alor District Trade Office. Data analysis was performed using SPSS 22.00. From the processed results of the questionnaire data, it is said to be valid because the person correlation value per statement item for each variable is more than the validity limit, which is 0.3, and is declared reliable. After all, Cronbach's alpha value for each variable is more than the reliability limit, which is 0.6. The research data passed the classical assumption test because they were normally distributed, there was no heteroscedasticity, there were no symptoms of multicollinearity and there was a linear relationship with the value of each test being greater than the alpha value of 0.5. Based on the research results obtained, it was concluded that the variables of work motivation, participative leadership, and organizational culture partially and simultaneously have a significant effect on employee performance. This is indicated by the significance value of the t-test or partial test on the work motivation variable of 0.001 or 0.1%, the significance value of the t-test on the participatory leadership variable is 0.012 or 1.2%, the significance of the t-test on the organizational culture variable is 0.019 or 1 .9% and simultaneously the variables of work motivation, participatory leadership, and organizational culture together have a significant effect on employee performance with a significance value of the F test of 0.000 or 0.0%.